2012
DOI: 10.1200/jop.2011.000500
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guidelines, the Politics of Value, and the Practice of Medicine: Physicians at the Crossroads

Abstract: Best practice guidelines are being used to an increasing degree, not only by physicians to improve the level of care, but also by bureaucrats to constrain reimbursement and guide the pathways of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although the summary recommendations can be interpreted as being very rigid, the guideline document puts these recommendations into context with plenty of room for personalization for individual patients. This context is especially important given that guidelines as a whole tend to be simplifications, which makes them easier to remember and implement but can result in the misclassification of individual patients 286,287 . In the 5 years since the publication of the KDIGO guideline, new clinical data has become available, novel therapies have emerged and other lipid management guidelines have been published.…”
Section: [H1] the Kdigo Clinical Practice Guidelinementioning
confidence: 99%
“…Although the summary recommendations can be interpreted as being very rigid, the guideline document puts these recommendations into context with plenty of room for personalization for individual patients. This context is especially important given that guidelines as a whole tend to be simplifications, which makes them easier to remember and implement but can result in the misclassification of individual patients 286,287 . In the 5 years since the publication of the KDIGO guideline, new clinical data has become available, novel therapies have emerged and other lipid management guidelines have been published.…”
Section: [H1] the Kdigo Clinical Practice Guidelinementioning
confidence: 99%
“…Practically, their use by physicians in the course of treatment decisions has proved to be invaluable. While cost is not implicit, philosophically guidelines operate at “value” level, a paradigm that links quality and cost 3 . Not surprisingly in West it is used to determine reimbursement of a procedure.…”
mentioning
confidence: 99%
“…Using the guidelines for quality care delivery depends on the judgment of only those physicians who are trained to cope with complexity and uncertainty and who understand the nuanced characteristics of their patients’ particular circumstances.Guidelines are expressions of the optimal pathway for the average patient, but, of course, most patients are not average 4 . As a matter of fact there is a possibility that the doctrinaire application of guidelines to all patients can be harmful as shown in a recent study which revealed that the inflexible use of the most widely accepted hypertension guidelines would lead to inferior outcomes 3 The measures of effectiveness of guidelines may be quite narrow, and many deal with processes of care or patient satisfaction, neither of which correlate with clinical outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 However, restricting flexibility in the treatment decision may in the end jeopardize patient-centered care. 4 Cooper and Strauss discuss their concern for the potential tyranny of guidelines in a recent paper, stating that “guidelines are expressions of the optimal pathway for the average patient, but, of course, most patients are not average (pp.233).” 5 Finding the correct balance between following guidelines and patient-centered care is relatively uncharted territory and open to scientific inquiry.…”
mentioning
confidence: 99%